Global Leadership Initiative on Malnutrition: a bibliometric analysis of research trends and contributions (2018–2024) - Xu, Qimeng; Li, Qiufu; Yao, Yucheng; He, Ying; Tan, Sitao; Liu, Xiaoxia; Chen, Xiaoyu (Frontiers in Nutrition, 2025)
BackgroundThe Global Leadership Initiative on Malnutrition (GLIM) criteria were officially introduced in 2018 with the aim of establishing a standardized global framework for the diagnosis of malnutrition. Synthesizing expert consensus from multiple international organizations, the GLIM criteria proposed a two-step diagnostic model integrating both phenotypic and etiologic components. Although GLIM-related research has expanded rapidly in recent years, a comprehensive bibliometric evaluation remains absent.MethodsRelevant literature published between 2018 and 2024 was retrieved from the Scopus database. Only English-language original research articles and reviews were included. A total of 729 eligible publications were analyzed using VOSviewer (v1.6.10), CiteSpace (v5.8.R3), and the online platform Bioinformatics. The analysis covered various dimensions, including countries, institutions, authors, journals, keywords, and highly cited references.ResultsThe volume of GLIM-related publications has shown a steady upward trajectory, peaking in 2024. China emerged as the most prolific country, followed by Spain and Japan. The top contributing institutions included Uppsala University, Capital Medical University, and Beijing Shijitan Hospital. Among the most productive authors were Cederholm T, Shi H, and Correia MITD. Clinical Nutrition and Nutrients were identified as the core journals in this field. Keyword analysis revealed that “malnutrition,” “diagnosis,” “sarcopenia,” “cancer,” and “nutritional risk” were pre-dominant themes, while “systematic review,” “protein blood level,” and “gastric cancer” represented emerging areas of interest.ConclusionThis study represents the first comprehensive bibliometric analysis of research related to the GLIM criteria. It identifies key contributors, collaboration networks, and thematic evolutions in the field, highlighting a transition from the development of diagnostic frameworks to clinical application and individualized nutritional assessment. These findings provide a valuable reference for guiding future research directions in GLIM-related domains.